Association of endocrine active environmental compounds with body mass index and weight loss following bariatric surgery. (9th June 2020) - Deshmukh, Harshal; Aylward, Lesa L.; Rose, Martin; Fernandes, Alwyn; Sedman, Peter; Thatcher, Natalie J.; Atkin, Stephen L.; Sathyapalan, Thozhukat
Abstract: Introduction: The objective of this study was to study associations of a wide range of halogenated biphenyls, dibenzo‐p‐dioxins, dibenzofurans and diphenylethers with body mass index (BMI) and evaluate changes in their concentration following bariatric surgery. Methods: Subcutaneous fat, visceral fat and liver tissue samples were collected from 106 patients undergoing Roux‐en‐Y gastric bypass surgery for weight loss or patients who were undergoing abdominal surgery for nonbariatric reasons. We measured concentrations of an extensive panel of chlorinated and brominated biphenyls, dioxins, and furans, and brominated diphenylethers in the samples. We conducted linear regression to examine associations with BMI, adjusting for age and gender. Changes in concentration for indicator chemicals were evaluated in samples collected following bariatric surgery in a small subpopulation. Results: After adjustments for age and gender and correction for multiple testing, seven ortho‐chlorinated biphenyls, one nonortho‐chlorinated biphenyl, four PCDD/Fs and one ortho‐brominated biphenyl were associated with BMI. The strongest associations between BMI and lipid‐adjusted concentrations were seen with PCB‐105 in subcutaneous fat (beta = 16.838 P ‐val = 1.45E‐06) PCB‐126 in visceral fat (beta = 15.067 P ‐val = 7.72E‐06) and PCB‐118 (beta = 14.101 P ‐val = 2.66E‐05) in liver. The concentrations of sum PCBs, chlorinated toxic equivalent quantity (TEQ's) and brominated compounds increased significantly with weight loss in subcutaneous fat in a group of ten individuals resampled up to five years after bariatric surgery and substantial weight loss. Conclusion: We show that selected polychlorinated biphenyls PCBs and structurally related polychlorinated dibenzo‐p‐dioxins dibenzofurans (PCDD/Fs) were associated with BMI. Concentrations of these lipophilic compounds in subcutaneous fat increased following bariatric surgery.